Improving the technology of part machining by surface plastic deformation - Dudnikov, Anatolii; Dudnikov, Ihor; Kelemesh, Anton; Gorbenko, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2019)
The purpose of this work is to study the technological process of strengthening hollow cylindrical parts of tractor engines using surface plastic deformation. Experimental studies in a wide range of changes in various factors have been preliminary performed on models. The data obtained were recalculated from the model to specific parts – piston fingers and bushings of the top heads of connecting rods in automotive tractor engines. The study was aimed at determining the efforts, stresses, changes in shape, the properties and structure of a parts’ material. In the course of our study, the law of similarity was maintained, whereby the sample models were geometrically similar and physically identical to parts. The rational shape of machining tools was experimentally established – conical; as well as its optimum dimensions: angle of inclination, 10°30’; magnitude of the calibration belt, 6–7 mm, which provide for the magnitude of strengthening and surface quality of the machined material. We have experimentally established the effect of angle of inclination of the machining tool on the amount of a metal sticking to its working surface. The dependence of the amount of a sticking metal on its hardness and the elasticity module has been established. We have determined the impact of height of the calibration part of a machining tool on the roughness of a part’s machined surface. The empirical dependence of machining allowance with a residual deformation along the outer diameter of a piston finger has been derived based on the laboratory data obtained. It has been found that the most dangerous are the tangential stresses along the outer surface of piston fingers, which were determined in the process of deformation by a strain gauge method. We have experimentally established the value of machining allowance over a single run of the working tool at vibration deformation of piston fingers, which ensures a reduction in tensile residual stresses. Our study into the static strength of piston fingers has found that the magnitude of wear depends on the following basic factors: a machining method, the material and time of operation. The research into the weight wear of piston fingers and bushings of the top heads of connecting rods has established that at vibration deformation the amount of wear is less compared to regular expansion. The magnitude of wear of the piston fingers restored by a vibration method is 1.13 times less than that in those restored by regular expansion